Planejamento estratégico na gestão de bibliotecas universitárias: um estudo de caso da biblioteca da Universidade Federal Rural da Amazônia - SILVA, Mariluce Iraneyde Ribeiro da (2017)
Strategic planning is an important tool that provides safety and assertiveness in the development of activities, and in decision making by their managers, passing by various sectors of the organization. Based on this premise, this study aims to identify the benefits of implementing this tool in the library of the Federal Rural University of Amazonia, aiming to understand its relationship with the strategic planning. The research carried out was performed by means of a case study, exploratory, using the techniques of collecting: documentary research, structured interview with the team of managers who are responsible for planning and participant observation, which were made to gather information. It is concluded that the use of strategic planning in university Libraries enables the visualization of where the unit wants to reach, establishes the management strategies and allows control and monitoring of results.